THE QUALITY OF ADMINISTRATIVE SERVICES IN INSTITUTE OF HEALTH SCIENCE, BINA MANDIRI GORONTALO - Ely Ibrahim (LP2M Universitas Bina Mandiri Gorontalo, 2021)
This research aims to know the quality of administrative services and inhibiting factors services in the Institute of Health Science, Bina Mandiri Gorontalo. Data were analyzed with descriptive qualitative, the data were obtained through field observation, interview, and documentation. While stage presentation of data with the data analysis, data reduction, and conclusions. The result of the research shows that Service Quality in the Institute of Health Science (STIKES ) Bina Mandiri Gorontalo, already well underway even meet the expectations of students and inhibiting factors services in Institute of Health Science, Bina Mandiri Gorontalo such as facilities and others while restyled. Suggested, that: 1) To better service and enhanced in terms of providing services to students, 2) Addition of human resources who has the capacity and competence in their respective fields, 3) find the solutions on how to be able to provide a comfortable waiting room and peaceful for students, 4) STIKES Bina Mandiri Gorontalo is expected to provide a safe parking place for vehicles, 5) For the development of the institution implemented gradually and continuously.